Oleuropein Protects against the Development of Kidneys Induced by Paracetamol in Albino Male Rats. - Ahmed Mejbel, Elham; Subhi Noori, Saif; shakir Mahmood, Adeeb; Riyadh Abdul Kareem Al-Hetty, Hussein; Musleh, Mohammed H. (HAYATI Journal of Biosciences, 2025)
Paracetamol treatment is considered one of the treatments used to relieve pain and antipyretic. Therefore, excessive doses and long-term use lead to organ toxicity. Paracetamol treatment is considered one of the treatments used to relieve pain and antipyretic. Therefore, excessive doses and long-term use lead to organ toxicity. The aim of the study was to investigate the protective effect of Oleuropein extracted from olive leaves on the physiological and histological aspects induced by Paracetamol in a rat model. The methods used 25 albino Swiss rats randomly distributed into five groups with the same number. The unit of control is given normal saline. Paracetamol (750 mg/kg) was injected into the group once. In the treatment groups (50 mg/kg, 100 mg/kg, 150 mg/kg). The Administration of Paracetamol's result significantly increased blood urea, creatinine, sodium, and potassium levels, and their blood concentrations decreased with Oleuropein (P 0.05). In addition, Oleuropein extracted from olive leaves relieved some symptoms, including acute vascular congestion caused by a dose of Paracetamol. Compared with paracetamol treatment, there is an infiltration of inflammatory cells and severe nephrotoxicity in the tubules. According to this study, the Oleuropein extracted from olive leaves can be used to prevent kidney damage, and It is not recommended to give Paracetamol, which increases kidney disorders.